Assessing Readiness Levels for Implementation of Industry 4.0 Technologies in Military Maintenance Depots (Advances in Military Technology, 2025)
Industry 4.0(I4.0) is transforming manufacturing and maintenance processes across various sectors in the world. This paper assesses I4.0 readiness levels in Indian Military Aircraft and Systems Maintenance Depots (MASMDs). Current readiness models often lack dimensions relevant for military maintenance. This research evaluates five diverse MASMDs across different platforms, analyzing data based on aircraft type, systems type, depot size, workload, and technological capabilities. The results reveal varying I4.0 readiness levels among depots and identify critical improvement areas. The findings provide insights for defense organizations planning digital transformation in maintenance facilities. Future research could extend to other military maintenance domains or compare readiness across different nations' armed forces.
Keywords: Industry 4.0; maintenance; military repair depots; readiness level